The Curtis Harrington Short Film Collection - Harrington, Curtis (Flicker Alley, 2013)
Curtis Harrington, widely regarded as one of the important avant-garde directors of the 1940's, as well as an early influential figure in what would come to be known as "New Queer Cinema", was born in Los Angeles in 1926. He began making films as a teenager, often deeply surreal, intuitive, and owing much to the writings of Edgar Allan Poe. After graduating from UCLA with a degree in film studies, his unique career trajectory led him from the academic circles of cinematic criticism; to the Hollywood assistant desk of writer/producer Jerry Wald; to the elite group of independent filmmakers associated with Kenneth Anger; to the famed film factory of cult icon Roger Corman; then on to his own stint in the world of genre movie-making with "Night Tide and Games"; and most unpredictable of all, to finding commercial success in television. [www.flickeralley.com]